(untitled) (Revista Latino-Americana de Enfermagem, 2011)
Cross-sectional study developed to relate the international normalized ratio (INR), used as a parameter to monitor the levels of blood clotting, stability to adherence, age, level of education, socioeconomic level, interaction with other drugs, comorbidities, vitamin K intake, anticoagulation time and drug cost. 156 patients were included, mean age 57±13 years, (53.8%) male, 61 (39.1%) had high adherence, 91 (58.3%) medium and 4 (2.6%) low adherence to treatment, 117 (75%) had INR stability up to 50% and 39 (25%) >; 75%, patients with shorter time of anticoagulation presented higher stability, those who spent less on the drug remained more stable and had better adherence. It was concluded that more than 90% of patients had high and medium adherence and that the anticoagulation time and drug cost were the factors related to the anticoagulation stability.